Advancing Inclusive Growth in Cambodia - Hansen, Niels-Jakob (IMF Working Papers; Working Paper ;, 2019)
We evaluate the impact of fiscal reforms on growth and inequality in Cambodia using a calibrated general equilibrium model with heterogeneous agents (Peralta-Alva and others, 2018). Over the last two decades, Cambodia's consumption inequality and poverty have declined. However, income inequality is higher, and large gaps remain between urban and rural residents. At the same time, domestic revenue mobilization has improved substantially, but collection of tax revenue is biased towards non-progressive sources. We use the model to evaluate the growth and inequality impact of reforms that increase infrastructure spending by raising (i) VAT, (ii) property tax, or (iii) personal income tax. We find that using property taxes delivers the largest increase in GDP and reduction in inequality. Reaping the gains from property taxation will however require additional investments in tax administration.